Hubungan Antara Jangka Waktu Pembinaan Dengan Penurunan Gejala-gejala Ketergantungan Narkotika - Haryanto Haryanto; Siti Rahayu Harditono (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 1997)
This study was intended to assess the effectiveness of religious in therapy rehabilitating drug addiction among adolescents in InabahÂ· 1, Pondok Pesantren Suryalaya. Tasikmalaya, West Java. The primary hypotheses was tested by calculating the correlation between durationof therapy and the decrease in drug addiction symptoms, which wasmeasured by "Physical Complaint Scales and Somatization Scales".Thirty five (35) adolescent drug abusers participated in this study. Pearson product moment correlation was used to analyze the relationÂship. The finding showed that duration of therapy was correlated withthe symptoms of drug addiction, was measured by physical complaint scales and was measured by somatization scales. It is suggested thatthe tonger the duration of the therapy, the shorter the symptoms ofdrugs addiction. Key words: drugs abused, religious therapy, Pondok PesantrenSuryataya